Health promotion, quality of life and health inequity: reflections for public health. - Aline Rodrigues de ALMEIDA; Filipe Tadeu Santanna ATHAYDE (Universidade de Brasília, 2016)
The idea of health promoting has become a major power in the movement of public health, on which health is a social phenomenon and marked for inequities. This work aimed to understand the relationship between health promotion and inequalities of access and health care, by identifyingthe barriers to an equal public health practice with emphasis on quality of life.The different profiles of disease and its social mediation beyond the studies of biological variation and incorporates a focus on the social dimension of vulnerability. To promote health in Brazil, is inseparable from facing a reality of major historical inequities that impose daily challenges not only to the health sector , but to all those who build public policies. The quality of life depends on the satisfaction of basic needs of all citizens, proposing a management based on social solidarity, a holistic view of the problems and reducing inequities. The health promotion in a country as unequal as Brazil proposes a constant challenge to the actors involved in the health system. The understanding of health inequalities to establish a holistic care is a difficult process, but extremely relevant to public health.